Analisis Rugi Daya Akibat Partial Discharge pada Generator Turbin Gas di North Duri Cogeneration Plant - Arzul, Arzul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The function of the generator is to produce electrical energy from the mechanical energy that rotates it. However, in a system for the generation of electrical energy, there are possibilities for interference with the generator which can cause the generator to suffer damage. One of the disturbances that often occurs in generators is short circuit faults. Short circuit disturbances in generators can be caused by various things, which is an example of an insulation failure in the stator winding is called Partial Discharge. The failure of the insulation that occurs in the stator winding is the most dominant cause of damage to the generator. However, in operation, many factors cause a decrease in the quality of the insulation of the stator winding, including pressure factors that are electrical, mechanical and thermal. Partial discharge in the generator stator winding can also cause power losses in the generator. Power loss occurs due to the control of electric charge within a certain time frame during the partial discharge activity. By using the formula calculation, the value of the power loss that occurs due to partial discharge can be identified and analyzed to determine the condition of the generator. Partial discharge measurements were carried out using the IRIS POWER TGA-BTM Portale Partial Discharge (PD) Monitoring tool and the PDLitePro software. The object of study is the North Duri Cogeneration Generator Unit 1. Based on the results of comparative analysis, the measured PD magnitude was 160 mV in the isolation of the generator stator winding Unit-1 Phase A, 134 mV in the isolation of the generator stator winding Unit-2 Phase B and 124 mV in the isolation of the generator stator winding Unit-3 Phase C entered into Typical PD category level (<75 % Summary of Statistics). In addition, the generator Unit-1 has the highest magnitude when compared to Unit-2 (134 mV) and Unit-3 (124 mV). However, in general, PD activity in Unit-1 winding isolation is still within safe limits up to 160 mV. The value of the power loss due to a significant partial discharge that occurred in the North Duri Cogeneration Plant generator was in phase A of all phases that occurred and occurred on March 25 2019 with a power loss value of 8.70 mW.